Factors influencing return to play following conservatively treated ankle sprain: a systematic review - Al Bimani, S. A.; Gates, L. S.; Warner, M.; Bowen, C. (The Physician and Sportsmedicine, 2019)
Background: Ankle sprain is a very common injury, yet uncertainty exists in what is appropriate time to return to play (RTP). Such guidance may inform treatment pathways and effective practice.